2010
DOI: 10.1002/wcc.64
|View full text |Cite
|
Sign up to set email alerts
|

Using adaptation tipping points to prepare for climate change and sea level rise: a case study in the Netherlands

Abstract: Studies on the impact of climate change and sea level rise usually take climate scenarios as their starting point. To support long-term water management planning in the Netherlands, we carried out a study that started at the opposite end of the effect chain. In the study we refer to three aspects of water management, flood defense, drinking water supply, and protection of the Rotterdam Harbour. We examined whether, and for how long, current water management strategies will continue to be effective under differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
236
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(247 citation statements)
references
References 31 publications
2
236
0
9
Order By: Relevance
“…Opposite to this, systems, which their current vulnerabilities have already been approached, and present a current low risk, such as the case of Rotterdam city located in Rhin river delta in Holland, may advance in strategies focused on future vulnerability conditions, which means an adaptation process different from the process assisting current relevant vulnerabilities. (Kwadijk, et al, 2010). In both cases, the delta of Ganges River or delta of Rhine River, we find similar situations of adverse hydro-climate events exposure (low elevation plateaus and expose to floods of fluvial or coastal origin) but with current vulnerability conditions very different which imply different adaptation needs as well.…”
Section: • Identification Of the Adaptation Needsmentioning
confidence: 52%
“…Opposite to this, systems, which their current vulnerabilities have already been approached, and present a current low risk, such as the case of Rotterdam city located in Rhin river delta in Holland, may advance in strategies focused on future vulnerability conditions, which means an adaptation process different from the process assisting current relevant vulnerabilities. (Kwadijk, et al, 2010). In both cases, the delta of Ganges River or delta of Rhine River, we find similar situations of adverse hydro-climate events exposure (low elevation plateaus and expose to floods of fluvial or coastal origin) but with current vulnerability conditions very different which imply different adaptation needs as well.…”
Section: • Identification Of the Adaptation Needsmentioning
confidence: 52%
“…In contrast to Kasprzyk et al (2013), we pursue a pro-active solution to the problem by using robust optimization. Robust optimization methods aim at finding optimal outcomes in the presence of uncertainty about input parameters that are not overly sensitive to any specific realization of the uncertainties (Ben-Tal andNemirovski 1998, 2000;Bertsimas and Sim 2004;Bai et al 1997;Kouvalis and Yu 1997). In robust optimization, the uncertainty that exists about the outcomes of interest is described through a set of scenarios (Mulvey et al 1995).…”
Section: Computational Support For Dappmentioning
confidence: 99%
“…Robustness can be operationalized in a wide variety of ways (see e.g. Rosenhead et al 1973;Wald 1945;Savage 1951;Simon 1955;Kouvalis and Yu 1997). In the EMA literature, robustness has been defined as the first order derivative of the objective function (McInerney et al 2012); as a reasonable performance over a wide range of plausible futures (Lempert and Collins 2007); relative, based on regret (Lempert et al 2003); and as sacrificing a small amount of optimal performance in order to be less sensitive to violated assumptions (Lempert and Collins 2007).…”
Section: Computational Support For Dappmentioning
confidence: 99%
“…We established the policy tipping points for various water management issues, including coastal protection and flood defense, and distinguishing between policy strategies and individual measures (Passchier et al 2009;Kwadijk et al 2010). This revealed that the present policy strategy can be continued for at least this century and probably several centuries to go, as long as the sea level rise does not exceed 1.5 m per century.…”
Section: The Present Netherlands' Flood Risk Management Policy: Tippimentioning
confidence: 99%